2017
DOI: 10.1038/srep41303
|View full text |Cite
|
Sign up to set email alerts
|

Culture adaptation of malaria parasites selects for convergent loss-of-function mutants

Abstract: Cultured human pathogens may differ significantly from source populations. To investigate the genetic basis of laboratory adaptation in malaria parasites, clinical Plasmodium falciparum isolates were sampled from patients and cultured in vitro for up to three months. Genome sequence analysis was performed on multiple culture time point samples from six monoclonal isolates, and single nucleotide polymorphism (SNP) variants emerging over time were detected. Out of a total of five positively selected SNPs, four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
90
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 43 publications
1
90
2
Order By: Relevance
“…Many parasites that have been in culture for a long time are loss-of-function mutants, with particular genes having acquired premature stop codons 15 , or having been lost in subtelomeric deletions 16 . Determining the true range of variation in asexual multiplication rate of P. falciparum would be an important step in being able to identify determinants of growth and virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…Many parasites that have been in culture for a long time are loss-of-function mutants, with particular genes having acquired premature stop codons 15 , or having been lost in subtelomeric deletions 16 . Determining the true range of variation in asexual multiplication rate of P. falciparum would be an important step in being able to identify determinants of growth and virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…Six of these shared hits have been linked to interaction with the host cell either via protein export or during the reinvasion process, while seven putatively function in gene regulation based on their predicted interaction with either RNA, DNA, or chromatin. These included two additional ApiAP2-family members, PF3D7_1139300 and PF3D7_1222400, a primate specific ApiAP2 recently found to acquire loss of function mutations in laboratory-adapted strains 17 . Four additional hits are implicated in the regulation of chromatin structure: two SNF2 family helicases (ISWI, SNF2L) that function in chromatin remodeling 18 and two putative histone modifying enzymes: the histone deacetylase HDA1 7 , and a previously un-annotated putative histone lysine-specific demethylase PfLSD2 (PF3D7_0801900, see Extended Data Fig.…”
mentioning
confidence: 99%
“…In transcriptomic studies of malaria parasites, achieving large numbers of replicate sample preparations is difficult, particularly from clinical isolates [5], and most current understanding is derived from a small number of parasite lines that have been culture-adapted for many years. Examination of genome sequences has identified premature stop codon mutants affecting some transcriptional factor genes and cell signalling protein genes [20,21], as well as particular gene deletions and amplifications only observed in parasites adapted to in vitro culture [22,23]. Although culture-adapted parasites are phenotypically and transcriptionally diverse [6,12,24], it is not clear to what extent they reflect the diversity of parasites causing clinical malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Much of our understanding of malaria parasite biology is derived from parasite lines that have been adapted to in vitro culture for decades [27-30]. Genome sequencing studies have identified polymorphisms in transcriptional factors and cell signalling proteins [31, 32], as well as genetic deletions and amplifications [33, 34] that are associated with adaptation of parasites to in vitro culture. While laboratory-adapted isolates are antigenically and transcriptionally diverse [3, 17, 26, 35, 36], it is not clear to what extent they reflect the diversity among ex vivo parasites.…”
Section: Introductionmentioning
confidence: 99%